Principled Disagreements: Adhesion to Intergroup Justice Standards in the Context of the Belgian Linguistic Conflict. Issue 3 (21st November 2017) - Klein, Olivier; Bouchat, Pierre; Azzi, Assaad; Luminet, Olivier
According to the "Waffle" model of the Belgian Linguistic Conflict (Klein et al., 2012 ), this conflict centres around two main dimensions: One concerns the use of language across the territory and the second concerns the distribution of resources between the two main linguistic communities, Dutch-speakers and French-speakers. The model suggests that the two groups adhere to different justice principles regarding these issues and that these disagreements are a function of the intensity of the conflict. With respect to the first dimension, Dutch-speakers are expected to adhere more to a principle of linguistic territoriality than French-speakers who should be more in favor of a free choice of one's idiom across the territory. With respect to the second dimension, the model posits that Dutch-speakers will adhere more to an equity principle whereas French-speakers should adhere more to a need principle. We tested these hypotheses in the context of a large-scale survey involving two waves: in May 2011 in the middle of a political crisis, and in June 2014, when the conflict was appeased. The pattern of "disagreements" in a subsample that participated in both waves of the survey ( N = 378) is consistent with the Waffle model and, as expected, more severe at the heart of the conflict (in 2011) than after pacification (in 2014). However, differences were driven mostly by supporters of the Flemish nationalist party N-VA. Moreover, endorsement of principles on both dimensions are predictive of separatist attitudes in the Dutch-speaking sample whereas only the first dimension plays a role for the French speaking sample.